Transformador eletrónico. Princípios de funcionamento e controlo - Xavier Ferreira da Silva (2019)
The technology of solid state transformers has captured the interest from both academia and industry. The various projects that have been carried out have demonstrated the potential of this technology as the basis of the future intelligent electric grid. In addition, the development of silicon carbide based semiconductor technologies has further contributed to the evolution of SST systems. This dissertation intends to carry out the study and comparison of the various topologies of conversion of SST systems, the study of the control systems, and the design of an SST conversion chain, and its control architecture.